Enhanced photocatalytic activity of Eu-doped Bi2S3 nanoflowers for degradation of organic pollutants under visible light illumination1. Issue 8 (21st August 2015) - Sarkar, Arpita; Ghosh, Abhisek Brata; Saha, Namrata; Dutta, Amit Kumar; Srivastava, Divesh N.; Paul, Parimal; Adhikary, Bibhutosh
<x xml:space="preserve">Abstract</x> Eu-doped Bi2S3 nanoflowers possess highly visible light driven photocatalytic activity towards degradation of organic pollutants.